2019
DOI: 10.2147/ott.s223258
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ultra-Low-Dose Bevacizumab For Cerebral Radiation Necrosis: A Prospective Phase II Clinical Study</p>

Abstract: ObjectiveTo investigate the treatment efficacy of ultra-low-dose bevacizumab for cerebral radiation necrosis.MethodsPatients with cerebral radiation necrosis after stereotactic radiotherapy (SRT) confirmed by imaging were included. Bevacizumab (1 mg/kg, once every three weeks, for at least three continuous treatments) was administered. The primary endpoints included change in cerebral necrosis symptoms, volume of intracranial edema, and changes in MRI signals. The secondary endpoints were adverse reactions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(66 citation statements)
references
References 30 publications
7
59
0
Order By: Relevance
“…Overall, two prospective studies, seven retrospective studies, and three case reports involving 89 patients with RN treated with BV were obtained following the research strategy and study selection process [33,[48][49][50][51][52][53][54][55][56][57][58]. The PRISMA flow diagram for the same is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, two prospective studies, seven retrospective studies, and three case reports involving 89 patients with RN treated with BV were obtained following the research strategy and study selection process [33,[48][49][50][51][52][53][54][55][56][57][58]. The PRISMA flow diagram for the same is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bevacizumab (BV) has also made it a treatment paradigm for RN [28][29][30]. Recent clinical trials have shown encouraging results [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One option would be to further lower the dose of bevacizumab but keep the continuous administration. This approach of lowering the dose to 1 mg/kg bevacizumab every three weeks has revealed promising results in a phase 2 trial [ 19 ]. The trial included 21 patients and the grade of the edema index was improved in 19 patients.…”
Section: Discussionmentioning
confidence: 99%